The Icelandic Concrete Saga: Architecture and Construction (1847–1958) - Sofia Nannini (Jovis)
“Many would consider a country without building materials uninhabitable.” With these words, Minister of Industry Gylfi Þorsteinsson Gíslason opened Iceland’s first and only cement plant in 1958. More than a century before, Portland cement was first used as plaster on the walls of the Reykjavík cathedral. At the time, most rural and urban dwellings were still being built from local turf or expensive imported timber. Just a few decades later, Icelandic architects, engineers, and masons were building their country exclusively in concrete. How did this material become so popular that the first decades of the twentieth century are referred to as “the age of concrete”? The Icelandic Concrete Saga focuses on over one hundred years of Icelandic architecture, construction, and technology. It traces the history of an architecture in constant struggle with material scarcity and the natural elements, its outcomes intertwined with Icelandic politics, culture, and society.